1998
DOI: 10.1016/s0014-5793(98)00684-x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of protein phosphatase 2A by cAMP‐dependent protein kinase‐catalyzed phosphorylation of the 74‐kDa B″ (δ) regulatory subunit in vitro and identification of the phosphorylation sites

Abstract: Human erythrocyte protein phosphatase 2A, which comprises a 34-kDa catalytic C subunit, a 63-kDa regulatory A subunit and a 74-kDa regulatory BQ (N N) subunit, was phosphorylated at serine residues of BQ in vitro by cAMP-dependent protein kinase (A-kinase). In the presence and absence of 0.5 W WM okadaic acid (OA), A-kinase gave maximal incorporation of 1.7 and 1.0 mol of phosphate per mol of BQ, respectively. The K m value of A-kinase for CABQ was 0.17 þ 0.01 W WM in the presence of OA. The major in vitro pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 24 publications
3
80
0
Order By: Relevance
“…Fig.13) and can phosphorylate nuclear DARPP-32 and promote its export. Stimulation of D1R triggers rapid phosphorylation of Thr-34 responsible for cytoplasmic effects of DARPP-32, and slower dephosphorylation of Ser-97 by activating PP2A through cAMP/PKA-mediated phosphorylation of its B56δ subunit 26,27 , thus decreasing the nuclear export of DARPP-32. Although phosphorylation has been reported to regulate cyto-nuclear shuttling of a number of proteins 35 , this is a rare example of facilitation of CRM1-mediated nuclear export by phosphorylation 36,37 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fig.13) and can phosphorylate nuclear DARPP-32 and promote its export. Stimulation of D1R triggers rapid phosphorylation of Thr-34 responsible for cytoplasmic effects of DARPP-32, and slower dephosphorylation of Ser-97 by activating PP2A through cAMP/PKA-mediated phosphorylation of its B56δ subunit 26,27 , thus decreasing the nuclear export of DARPP-32. Although phosphorylation has been reported to regulate cyto-nuclear shuttling of a number of proteins 35 , this is a rare example of facilitation of CRM1-mediated nuclear export by phosphorylation 36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Fig.9a), and is activated by cAMP-dependent phosphorylation 26,27 . When B56δ was co-expressed with DARPP-32 in HEK293 cells, it promoted dephosphorylation of Ser-97 in response to forskolin (Fig.3e, Supp.…”
Section: Dopamine and Camp Trigger Dephosphorylation Of Ser-97 Througmentioning
confidence: 99%
See 1 more Smart Citation
“…Regulatory subunits are subdivided into PR55 B, PR56 BЈ, PR72 BЉ, and PR61 families (20,21). Usui et al reported that the regulatory BЈ␦ subunit (or B56␦), originally purified from erythrocytes and named the BЉ (␦) subunit, is phosphorylated by PKA and that phosphorylated forms of BЈ␦ stimulate the catalytic activity of PP-2A in a substrate-specific manner (22,23). Immunoblot analysis using BЈ␦ antibody revealed that the level of expression of the protein was slightly higher in striatum than in neocortex (A.N., unpublished observations), the region in the central nervous system in which the level of expression of BЈ␦ was reported to be most abundant (24).…”
Section: Discussionmentioning
confidence: 99%
“…The reaction products were analyzed by SDS-PAGE, followed by autoradiography. For the in vitro kinase assay using [␥- 32 P]ATP, bacterially produced and purified His-tagged Arix proteins (1 g) (14) were incubated at 30°C for 5 min with 10 ng of rPKA in the kinase reaction buffer containing 12.5 mM Tris-Cl (pH 8), 0.1 mM ATP, 10 mM MgCl 2 , 0.25 mg/ml bovine serum albumin, and 0.5 Ci [␥- 32 P]ATP. The reaction was stopped by adding EDTA at the final concentration of 80 mM on ice.…”
Section: Methodsmentioning
confidence: 99%